Vytváření mikrostruktur dvoufotonovou fotopolymerací - Skalický, Jiří (Vysoké učení technické v Brně. Fakulta chemická, 2015)
Využití fokusovaného laserového svazku k iniciaci fotopolymerace představuje elegantní a rychlou metodu, jak získat mikrostruktury o rozměrech od stovek nanometrů po desítky mikrometrů. K získání mikrostruktur se submikrometrovými detaily se využívá dvoufotonové fotopolymerace, kdy vlnová délka laseru je přibližně dvojnásobná s ohledem na spektrální citlivost fotorezistu a k iniciaci fotopolymerace dochází pouze v místech, kde je dostatečná optické intenzita. Přesným řízeným polohováním fotorezistu vzhledem k ohnisku svazku lze osvítit pouze oblasti budoucí mikrostruktury a iniciovat zde fotopolymeraci. Jemné detaily vytvořených struktur závisí kromě míry fokusace svazku i na zvoleném fotorezistu a zhášení polymerace v neosvícených oblastech.

Utilization of focused laser beam for photo-polymerization represents an elegant and fast method how to manufacture microstructures in dimensions from hundreds of nanometres to tens of micrometres. Two-photon photo-polymerization is used with advantage to manufacture microstructures with sub-micrometre details. In this case the laser wavelength is about two times longer comparing to the spectral region of the highest photoresist sensitivity and the two-photon photo-polymerization is initiated only in the positions of sufficient optical intensity. Precise and controlled positioning of the photoresist with respect to the laser focus ensures only illumination of areas of future microstructure and initialization of photo-polymerization here. Fine details of manufactured microstructures depends, except the laser beam focusing, also on the chosen photoresist and quenching of polymerization in non-illuminated areas.
Manufacturing of micro-structures by two-photon polymerization
Keywords: fotopolymerace; mikrostruktury; dvoufotonová fotopolymerace; fs laser; fokusace laserového svazku; photo-polymerization; microstructures; two-photon absorption; fs laser; focusing of laser beam